Oxygen yields as a constraint on feedback processes in galaxies - Lara-López, Maritza A.; De Rossi, Maria Emilia; Pilyugin, Leonid S.; Gallazzi, Anna; Hughes, Thomas M.; Zinchenko, Igor A. (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. We study the interplay between several properties determined from optical and a combination of optical/radio measurements, such as the effective oxyg